The technical-creative process in the translation of children’s literature: Between words and flavors - Bunn, Daniela (2019)
These reflections, which resulted from a project developed by Cuca Fresca publisher, aim at socializing some experiences in the field of Children’s Literature Translation, from Portuguese to Italian. Two books were translated and published in 2011, Mariolino e Luigino and La casa della nonnina è troppo carina. The books present scenes of the everyday family life and their translations seem to offer an interesting and differentiated material that may contribute to the diffusion of Italian language. This discussion also aims at evaluating the difficulties, the importance and the peculiarities of Children’s Literature Translation in relation to textual and visual elements. The reflections and translations developed in this work, are a mixture of knowledge and pleasure. Pleasure with the stories and with the technical-creative and recreative process.